A two-level plane wave time-domain algorithm for fast analysis of EMC/EMI problems - Aygün, K; Shanker, B; Ergin, AA; Michielssen, E (IEEE-Inst Electrical Electronics Engineers Inc, 2002)
In this paper, a fast time-domain integral equation (IE)-based scheme for analyzing transient electromagnetic compatibility and interference (EMC/EMI) problems involving printed circuit boards and cables/connectors that reside in shielding enclosures, is presented. The proposed algorithm hybridizes a classical marching-on-in-time (MOT) solver for analyzing radiation from perfect electrically conducting (PEC) surface/wire geometries with the recently introduced two-level plane wave time-domain (PWTD) algorithm. The accuracy and efficacy of the resulting MOT-PWTD algorithm are validated via analysis of the radiation characteristics of a number of structures including a loaded motherboard that resides in a chassis. For a problem with N-S spatial and N-T temporal unknowns, the computational complexity of the two-level MOT-PWTD algorithm scales as O(NTNS1.5 log N-S) as opposed to O (NTNS2) for a classical MOT scheme.
Keywords: computational complexity; electromagnetic compatibility; electromagnetic interference; integral equations; PWTD